VD_FINDINFO PPD 23/10 - 28/2011 vom 1. März 2011 - VD Tribunal cantonal (2011)
PARTAGESENS GÉNÉRAL, PRESTATION DE PRÉVOYANCE, DROIT INTERNATIONAL PRIVÉ, JUGEMENT DE DIVORCE | 122 al. 1 CC, 63 LDIP, 22 al. 1 LFLP, 12 OPP2